Influence of culture conditions on a mycelium-bound lipase production from Aspergillus niger MYA 135 - Colin, Veronica Leticia (2007)
Introduction: Lipases (EC 3.1.1.3) are enzymes that hydrolyse the ester bonds of water insoluble substrates at the interface between the substrate and the water. This reaction is reversible. Lipases may also catalyze ester synthesis and transesterification in reaction mixtures with low water contents. Objective: The aim of this work was to study the influence of culture conditions on a mycelium-bound lipase production from Aspergillus niger MYA 135. Materials and methods: The fermentation medium comprised (in g/l): sucrose 10; NH4NO3 2; KH2PO4 1; MgSO4.7H2O 0.2; CuSO4.5H2O 0.06. The effect of modification in the environmental condition on lipase production was tested by changing the initial pH of the medium as well as by the addition of CaCl2, FeCl3 or Tween (20, 40, 60, and 80). Lipase activity was determined using 0.01 g of wet mycelium and p-nitrophenyl palmitate as substrate. Results and conclusions: The assayed culture conditions scientifically influences the lipase production. The highest specific activity (36.6 mU/g of DW) was obtained with either initial pH 8 or in presence of 0.5% Tween 60. This work was supported by grants PIP 6062 and PICTO 761.